1986
DOI: 10.1143/jjap.25.l121
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Polysilicon Super-Thin-Film Transistor (LSFT)

Abstract: Advanced polysilicon SFT's (Super-thin-Film Transistor) were fabricated on quartz at a low temperature process below 610°C. Using the technique of Si+ ion implanted amorphization and subsequent solid phase growth and making a super-thin-film structure, superior electrical characteristics such as high electron mobility of 60 cm2/(V·s) were obtained. The oscillation of a 19 stage ring oscillator with a channel length of 8.4 µm was observed. Propagation delay time of 8.13 ns/stage was attained. The device is expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(15 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…In order to integrate peripheral driving circuits on the same glass substrate, both a large current drive and a high drain breakdown voltage (BV) are necessary for poly-Si TFT device characteristics. It has been previously reported that the use of a thinner active channel film is beneficial for obtaining a higher current drive [3], [4]. The use of a thin active channel layer, however, inevitably results in poor SD contact and large parasitic series resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In order to integrate peripheral driving circuits on the same glass substrate, both a large current drive and a high drain breakdown voltage (BV) are necessary for poly-Si TFT device characteristics. It has been previously reported that the use of a thinner active channel film is beneficial for obtaining a higher current drive [3], [4]. The use of a thin active channel layer, however, inevitably results in poor SD contact and large parasitic series resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we proposed a temperature sensor employing a ring oscillator composed of poly-Si TFTs [14]. Although ring oscillators have been utilized to evaluate transistor characteristics [15]- [17], we believe that this was the first report to apply a ring oscillator to a temperature sensor. Incidentally, TFTs with lightly-doped drain structure (LDD TFTs) are indispensable to reduce off-leakage currents and avoid characteristic degradation [18]- [24].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6]. The outstanding advantage is that the reliability under severe bias and temperature stress is higher than those of amorphous-Si TFTs [7] and low-temperature poly-Si (LTPS) TFTs [8].…”
Section: Introductionmentioning
confidence: 99%